Perbandingan Kejadian Klinis Kardiovaskular Mayor Selama Perawatan di Rumah Sakit pada Penderita Infark Miokard Akut Elevasi Segmen ST Inferior Dengan dan Tanpa Depresi Segmen ST Prekordial - Jaya Suganti; Abdullah Afif Siregar; Harris Hasan (The Indonesian Heart Association, 2016)
Background: The clinical implications of precordial ST segment depression (PSTD) during acute inferior myocardial infarction has been an area of debate, and still under investigation with conflicting results. Based on previous studies, the presence of PSTD defines a high risk subset of patients with acute inferior myocardial infarction due to a more extensive myocardial ischemia that lead to a higher incidence of major adverse cardiovascular events (MACE). Despite of these results, others still considered this ECG finding as a benign electrical phenomenon. The aim of this study is to compare the incidence of in-hospital MACE in patients of acute inferior myocardial infarction with or without PSTD and to know whether PSTD can be used as a predictor of in-hospital MACE in acute inferior myocardial infarction.Methods: A total of 96 acute inferior myocardial infarction patients admitted from December 2013-2015 at Cardiology Department of Haji Adam Malik General Hospital were retrospectively analyzed. Patients were divided into two groups based on the presence of PSTD on admission ECG. Bivariate and multivariate analyses were performed to study the association between PSTD and in-hospital MACE, p value<0.05 was considered statistically significant.Results: The bivariate analysis showed that in-hospital MACE was significantly higher in patients of acute inferior myocardial infarction with PSTD than without PSTD (92% vs 8%, p<0.001). On multiple logistic regression analysis, patients of acute inferior myocardial infarction with PSTD have a 5.4 fold increased risk of in-hospital MACE than patients without PSTD (OR 5.480; 95% CI 1.759-17.067, p=0.003).Conclusion: The presence of precordial ST segment depression on admission ECG in acute inferior myocardial infarction patients was associated with a higher in-hospital MACE and was an independent predictor of in-hospital MACE.